Expanding criteria for slow colonic transit in patients being evaluated for chronic constipation by scintigraphy. Issue 9 (12th May 2020) - Khoshbin, Katayoun; Busciglio, Irene; Burton, Duane; Breen‐Lyles, Margaret K.; Camilleri, Michael
Abstract: Background: Colonic transit measurement [geometric center (GC) at 24 and 48 hours] identifies slow transit constipation (STC) in patients with chronic constipation. Aim: To evaluate the utility of the difference between GC24 and GC48 (Δ48‐24 ) to identify STC in adults with chronic constipation. Methods: We reviewed medical records of 250 patients, aged 18‐75 years, who underwent colonic transit by scintigraphy during 1994‐2019 for investigation of chronic constipation. Data collected included demographics, medical and surgical histories, and anorectal manometry. We used colonic transit from 220 healthy controls to identify the 5th percentile for diagnosing STC: 1.3 at 24 hours, and 1.9 at 48 hours. In addition, the 5th percentile for Δ48‐24 was 0.38 for females and 0.29 for males. Data are reported as median and IQR [Q1, Q3]). Key results: Among the 250 patients [median age 42.5 years (IQR 30.75, 56), 84% female], based on GC24 < 1.3, 52 (20.8%) had STC (3 males, 49 females); and based on GC48 < 1.9, 28(11.2%) had STC (3 males, 25 females). Colonic transit was normal in 74.8%. In the groups with normal GC24 and GC48, Δ48‐24 identified an additional 32(15.1%) of 212 female patients and 4 (10.5%) of 38 male patients with slow progression of colonic transit between 24 and 48 hours. Among these 36 patients with abnormal Δ48‐24, 13(36.1%) had evidence of rectal evacuation disorder. Conclusions & Inferences: Δ48‐24 measurement on scintigraphic colonic transit can identify an additional 9.2% of STC in patients with constipation without rectal evacuation disorder and can help individualize treatment of chronic constipation. Abstract : Measurement of colonic transit by scintigraphy (upper left) identifies patients with slow transit at 24 and 48 hours, summarized as geometric center (lower left) (data points below dashed line in lower right), and also patients with slow progression of isotope through the colon (upper right) as shown by the low ΔGC48‐24h (lower right).